Improvement of low-cost solar-powered desalination technologies in low-light intensity - Hossein Bahrami; Mohammad derayatifar; Seyyed Ehsan Shakib (Energy Conversion and Management: X)
Enhancing the efficiency of low-cost solar-powered desalination technologies, such as solar stills (SS), is essential for ensuring continuous access to freshwater in remote, water-stressed areas, particularly during cloudy or rainy days when the performance of conventional SS systems is compromised. This study introduces an innovative stepped solar still design, optimized for ease of operation, maintenance, environmental compatibility, and improved efficiency, especially under low-light conditions. The impact of the inlet mass flow rate on the desalination process was investigated to enhance distilled water production. Light absorption and step hot spot temperatures were further improved by incorporating natural and cost-effective absorbers, such as carbon, and an innovative soil-carbon combination. The synergy of this soil-carbon combination, enhancing light absorption, heat transfer, and storage through increased surface contact during radiation exposure and its distribution during shutdown, led to a 12.8% and 3% increase in distilled water production over the 4-hour test duration, compared to the baseline and carbon-only tests, respectively. This innovative design, combined with the use of a soil and carbon mixture, significantly improves the performance of solar distillation systems. These findings contribute to the development of sustainable, low-cost, and energy-efficient solutions for freshwater provision in remote areas, addressing both water scarcity and energy conservation challenges.